2021
DOI: 10.1017/s104795112100233x
|View full text |Cite
|
Sign up to set email alerts
|

State of the science and future research directions in palliative and end-of-life care in paediatric cardiology: a report from the Harvard Radcliffe Accelerator Workshop

Abstract: Workshop proceedings, priorities, and recommendations from the “State of the Science and Future Directions in Palliative and End-of-Life Care in Pediatric Cardiology,” a Harvard Radcliffe Accelerator Workshop, are detailed. Eight priorities for research were identified, including patient and family decision making, communication, patient and family experience, patient symptom measurement and management, training and curriculum development, teamwork, family hardships and bereavement, and ethical considerations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…ACTION (Advanced Cardiac Therapies Improving Outcomes Network) has demonstrated the feasibility of collecting patient-reported outcomes (PROs), including HRQOL, in pediatric and young adult patients pre-VAD implant and throughout the VAD course. Continued study of the utility of PROs to inform clinical practice and predict outcomes is needed [ 38 , 39 ]. This can be accomplished through multi-center learning network collaborations and registries, such as those hosted by ACTION and Pedimacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACTION (Advanced Cardiac Therapies Improving Outcomes Network) has demonstrated the feasibility of collecting patient-reported outcomes (PROs), including HRQOL, in pediatric and young adult patients pre-VAD implant and throughout the VAD course. Continued study of the utility of PROs to inform clinical practice and predict outcomes is needed [ 38 , 39 ]. This can be accomplished through multi-center learning network collaborations and registries, such as those hosted by ACTION and Pedimacs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, multi-center studies would allow for larger, racially, and ethnically diverse samples, increasing our understanding of these important factors. As this study demonstrates, discrepancies in patient and proxy/parent report exist, thus, we must continue to engage AYAs themselves in research to better understand their healthcare needs and outcomes [ 39 , 40 ]. With advanced statistics, such as machine learning, we may be able to better understand risk and resilience factors, including sex and race, smaller samples of pediatric heart failure patients with regards to HRQOL, physical, and psychosocial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Research on patient communication and medical decision-making was recently identified as a top priority for investigation specific to palliative and end-of-life care in pediatric cardiology, consistent with a National Academy of Medicine call for research on communication and shared decision-making in AYA serious illness . The current study aimed to characterize communication and medical decision-making preferences of AYAs with advanced heart disease and determine factors associated with these preferences to inform the timing, targets, and potential outcomes of future interventions.…”
Section: Introductionmentioning
confidence: 86%
“…11,12 Building upon these initial studies, increased understanding of circumstances surrounding death, including location of death and interventions performed at end-of-life in a large, multisite sample, will enable the pediatric transplant community to move forward with guidelines and interventions to improve the quality of care patients and families receive at a child's end-of-life. Thus, in response to calls for increased research study, 13 Patients were stratified into two cohorts: 1) pre-transplant (waitlist) and 2) post-transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon these initial studies, increased understanding of circumstances surrounding death, including location of death and interventions performed at end‐of‐life in a large, multisite sample, will enable the pediatric transplant community to move forward with guidelines and interventions to improve the quality of care patients and families receive at a child's end‐of‐life. Thus, in response to calls for increased research study, 13 this Pediatric Heart Transplant Society (PHTS) registry analysis study aimed to 1) describe the circumstances surrounding death of pediatric heart transplant patients, including transplant status at time of death, primary and contributing causes of death, location of death, and use of technological interventions at end‐of‐life and 2) examine associations between location of death and technological interventions at end‐of‐life with demographic, disease, and transplant‐related factors.…”
Section: Introductionmentioning
confidence: 99%